Adjustable double-pulse laser output based on diffraction loss modulation of acousto-optic Q-switching. (August 2022) - Wang, Hongyang; Zhang, Zhiyan; Yu, Haijun; Zhao, Shusen; Dong, Zhiyong; Cao, Kaixuan; Liu, Zhe; Lin, Xuechun
Highlights: Theoretical model calculation of double-pulse laser output based on acousto-optic Q-switch diffraction loss control. The double pulse waveform can be adjusted by programming: the pulse energy ratio and sub-pulse interval can be adjusted. The laser output results can match the calculated results of the model. The damage to the optical fiber can be largely avoided without reducing the laser cleaning efficiency. Abstract: We propose a gain control method for acousto-optic Q-switched lasers. The laser in single-pulse mode can be converted into a double-pulse mode with adjustable subpulse intervals and energy ratios. It reduces the peak energy density while keeping the total energy unchanged in a cycle and thus effectively avoids damage to the optical fiber. The gain of the beam can be controlled by modulating the diffraction loss in the resonant cavity. A theoretical model of acousto-optic Q-switched double-pulse laser is established. Double-pulsing with adjustable subpulse intervals and energy ratios can be designed. A double-pulse laser is built experimentally, and the actual output waveform is basically consistent with the calculated results of the theoretical model. A double-pulse laser with adjustable energy ratios, adjustable subpulse intervals of 500 ns–20 µs, and 127 W at 5 kHz can be obtained. In addition, laser paint removal experiments are conducted, proving that the double-pulse laser has the same cleaning ability as the single-pulse laser at the same average output power. At the same time, the damage to the optical fiber can be largely avoided.